A review of malaria molecular markers for drug resistance in Plasmodium falciparum and Plasmodium vivax in China - Wang, Siqi; Huang, Fang; Yan, He; Yin, Jianhai; Xia, Zhigui (Frontiers in Cellular and Infection Microbiology, 2023)
China has now achieved the elimination of malaria, but it still faces severe challenges in the post-elimination stage. China continues to be plagued by imported malaria cases, and preventing re-transmission of imported malaria is critical. The effectiveness of antimalarial drugs for malaria control largely depends on the study of drug resistance markers in vitro. Monitoring molecular markers of parasite-associated drug resistance can help predict and manage drug resistance. There is currently a lack of systematic reviews of molecular markers for indigenous and imported malaria in China. Therefore, this review summarizes the published articles related to molecular marker polymorphism of indigenous and imported malaria cases in China in the past two decades, to study the mutation frequency and distribution of crt, mdr1, dhps, dhfr and K13 gene resistance-related loci. This can provide a whole picture of molecular markers and the resistance mutations of imported cases in China, which has certain significance for drug resistance surveillance planning, safe and effective treatment, and preventing the recurrence of local transmission by imported malaria in China in the future.